The Central European buffer zone - Claire Wallace (European Regional Science Association (ERSA), 1998)
This paper considers the creation of a new region in Europe since the opening of the borders following the so-called "revolutions" in East-Central Europe. The "buffer zone" consists of a privileged group of post-Communist countries sandwiched between some of the most affluent countries of the European Union on the one side and countries with collapsing, unreformed or backward economies on the other. This paper considers the countries: Poland, Czech Republic, Hungary and Slovakia in terms of the circulation of GOODS, CAPITAL and PEOPLE around the region. The Central European buffer zone countries represent the most successful group of countries in terms of economic and political reform and social stability. This is both a cause and consequence of their attracting investment, tourism and other forms of economic and cultural communication from their neighbours to the west -. Especially Germany and Austria. For the countries to the East and South of the buffer zone, their prosperity and the possibility of crossing into the buffer zone but not further, creates an attraction for visitors from the East who arrive for settlement for work, for shopping, for trading or for establishing businesses. The establishment of cross-border communications depends to a large extent on reviving family, ethnic and cultural ties which were for many years severed by Communism.
Keywords: 330